Cryptographic key distribution using artificial intelligence for data security and location privacy in VANET. (3rd October 2022) - Kaushik, Shivkant; Poonia, Ramesh Chandra; Khatri, Sunil Kumar
Abstract: Location privacy & data security in VANET are now becoming most important in today's paradigm of information age. Unauthorized access to location information of vehicles may pose a significant security threat, thus it is necessary to secure this information from intruders. In proposed work, Artificial intelligence based RF range approximation is used with multi key controlled cryptography for enhancement of location privacy and data security in service location protocol of VANET'S.